2006
DOI: 10.1103/physrevlett.97.227402
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Disorder in Semiconductors via Single-Photon Interferometry

Abstract: The method of angular photonic correlations of spontaneous emission is introduced as an experimental, purely optical scheme to characterize disorder in semiconductor nanostructures. The theoretical expression for the angular correlations is derived and numerically evaluated for a model system. The results demonstrate how the proposed experimental method yields direct information about the spatial distribution of the relevant states and thus on the disorder present in the system.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 22 publications
(42 reference statements)
1
10
0
Order By: Relevance
“…7,8 The relationship between localized structural disorder and optoelectronic modification is critical in understanding the behavior of materials that necessarily have some amount of disorder, e.g., devices operating in a radiative environment, or a nanoscale structure where a single defect might dominate the device properties. 11,12 As pointed out by Bozsok, 9 while high-resolution microscopy can probe atomicscale structural disorder, this relationship between structural disorder and optical modification is still not well established. Here, we use coherent acoustic phonon (CAP) spectroscopy to measure optical modification caused by ion bombardment in GaAs wafers.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…7,8 The relationship between localized structural disorder and optoelectronic modification is critical in understanding the behavior of materials that necessarily have some amount of disorder, e.g., devices operating in a radiative environment, or a nanoscale structure where a single defect might dominate the device properties. 11,12 As pointed out by Bozsok, 9 while high-resolution microscopy can probe atomicscale structural disorder, this relationship between structural disorder and optical modification is still not well established. Here, we use coherent acoustic phonon (CAP) spectroscopy to measure optical modification caused by ion bombardment in GaAs wafers.…”
mentioning
confidence: 98%
“…5,6 Local structural modification surrounding a given defect site also modifies the lattice potential. [7][8][9][10] Neighboring atomic potentials experience strain-induced perturbations resulting in variations from the Bloch-like electronic wave functions that characterize an ideal periodic crystal, leading to nanoscale "pockets" of modified optoelectronic properties. The length scale over which such disorder will modify optoelectronic properties is generally not well-characterized and will vary for different material systems, although experiments in quantum wells have shown that the disorder potential can reach at least tens of nanometers.…”
mentioning
confidence: 99%
“…This technique has achieved a great success in numerous applications in semiconductor optics for systems with strong many-body correlations [4,5]. Our experience shows that the interplay of disorder and interaction does yield novel and interesting phenomena [6,7]. Here we provide one more evidence that it can also be used to tackle challenging problems in the field of interacting disordered systems.…”
mentioning
confidence: 85%
“…Here, E 1 and E 2 are the limits of the energy scan carried out in the experiment. U (x) is called the reconstructed disorder potential [11].…”
Section: A Reconstruction Proceduresmentioning
confidence: 99%
“…In order to enhance our understanding of the role of disorder in these systems, we have recently proposed an experimental scheme [11] which can be viewed as the Fourier analogue of nano-or microluminescence [12,13,14,15]. This scheme is based on measuring angular correlations of spontaneously emitted light and has been shown to give direct access to the spatial distribution of the optically active electronic states and to the effect of disorder on them.…”
Section: Introductionmentioning
confidence: 99%